A COMPARATIVE ASSESSMENT OF CLINICAL PROFILE AND IN- HOSPITAL OUTCOMES OF ST-ELEVATION MYOCARDIAL INFARCTION IN DIABETIC AND NON-DIABETIC PATIENTS: A CROSS-SECTIONAL ANALYTICAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetes mellitus is a major cardiovascular risk factor that significantly alters the clinical presentation and prognosis of ST-elevation myocardial infarction (STEMI). Diabetic patients often present with atypical symptoms and experience worse short-term outcomes compared to non-diabetic patients. This study was conducted to compare the clinical profile and in-hospital outcomes of STEMI in diabetic and non-diabetic patients. Objectives: To compare the clinical presentation, infarct characteristics, and in-hospital outcomes of STEMI among diabetic and non-diabetic patients. Materials and Methods: This cross-sectional analytical study was conducted at a tertiary care teaching hospital over a period of six months. A total of 80 patients diagnosed with STEMI were included, comprising 40 diabetic and 40 non-diabetic patients. Data regarding demographic characteristics, risk factors, clinical presentation, electrocardiographic findings, echocardiographic parameters, in-hospital complications, and mortality were collected using a predesigned proforma. Statistical analysis was performed using appropriate tests, and a p value of less than 0.05 was considered statistically significant. Results: Diabetic patients presented at a significantly higher mean age compared to non-diabetic patients. Silent or painless myocardial infarction was significantly more common among diabetics. Extensive anterior wall myocardial infarction and reduced left ventricular ejection fraction were observed more frequently in the diabetic group. Diabetic patients had a higher prevalence of systemic hypertension and higher Killip class at presentation. In-hospital complications, including cardiac failure and life-threatening arrhythmias, were significantly more frequent among diabetic patients. In-hospital mortality was higher in diabetics compared to non-diabetics. Conclusion: Diabetes mellitus is associated with an adverse clinical profile and poorer in-hospital outcomes in patients with STEMI. Early recognition of atypical presentations and aggressive management strategies are essential to improve short-term outcomes in diabetic patients with STEMI.